2020
DOI: 10.1105/tpc.19.00806
|View full text |Cite
|
Sign up to set email alerts
|

Phylotranscriptomics of the Pentapetalae Reveals Frequent Regulatory Variation in Plant Local Responses to the Fungal Pathogen Sclerotinia sclerotiorum

Abstract: Comparative transcriptome analyses reveal a major contribution of regulatory divergence in conserved genes during the response of Pentapetalae plants to the fungal pathogen Sclerotinia sclerotiorum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 103 publications
2
45
0
Order By: Relevance
“…This approach, however, does not completely exclude false-positive or false-negative AS events, and also does not (Zhao et al, 2013), is required to distinguish between these possibilities. In the current study, we limited our analysis to one stage of infection per host species, selected to represent similar infection stages on each host (Sucher et al, 2020). A time-course experiment as, for example, performed for Brassica napus (Seifbarghi et al, 2017)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach, however, does not completely exclude false-positive or false-negative AS events, and also does not (Zhao et al, 2013), is required to distinguish between these possibilities. In the current study, we limited our analysis to one stage of infection per host species, selected to represent similar infection stages on each host (Sucher et al, 2020). A time-course experiment as, for example, performed for Brassica napus (Seifbarghi et al, 2017)…”
Section: Discussionmentioning
confidence: 99%
“…This prompted us to test for AS in S. sclerotiorum during the infection of diverse host plants. To this end, we exploited RNA‐seq data of S. sclerotiorum infecting host plants from six botanical families, that is, Arabidopsis thaliana (Brassicales), tomato (Solanales), sunflower (Asterales), beetroot (Caryophyllales), castor bean ( Ricinus communis , Malphigiales), and common bean (Fabales), in addition to the RNA‐seq of S. sclerotiorum cultivated in vitro as control (Peyraud et al, 2019; Sucher et al, 2020). We found that S. sclerotiorum has a functional splicing machinery and that at least 4% of the S. sclerotiorum secretome undergoes AS regulation, resulting in multiple differentially expressed isoforms that may have modified or altered functions.…”
Section: Introductionmentioning
confidence: 99%
“…Letters indicate significance determined by pairwise Student's t-tests (p <0.01). (Adapted from Sucher et al [2020] Figure 2A and 2C).…”
mentioning
confidence: 99%
“…One such exception was the evolutionarily conserved response of a group of ABCG (ATP-BINDING CASETTE G) transporters to Sclerotinia infection across the Pentapetalae. Since Sclerotinia evolved more recently than the radiation of the Pentapetalae, Sucher et al (2020) reasoned that the Sclerotinia-related expression of ABCG orthologs occurred via exaptation from comparable ancestral stress responses. In support of this, publicly available expression data identified an A. thaliana ABCG40 ortholog consistently induced during bacterial or fungal infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation